Impact of integrating local culture into language materials on communicative ability of Malaysian lower secondary learners - Radha M K Nambiar,; Ruzy Suliza Hashim,; Ruhizan Mohammad Yassin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The importance of culture in learning a language is widely acknowledged even if the integration of culture into language learning and teaching materials has seen various opinions and approaches. Bearing in mind the ultimate aim of learning a language is for communication it is important materials developed for language learning consider content knowledge and linguistic knowledge. This paper discusses the impact of a supplementary reading module designed to improve communicative ability and cultural awareness with the integration of local culture. Focus group interviews were run over a three -year period with lower secondary students and English language teachers to elicit their perspectives on the value of the module and the benefits in helping to develop better communicative ability. Both teachers and students were asked similar questions about their opinions of the module, opinions about the lessons and on the use of English to teach the module. The responses matched with both claiming the module was interesting, attractive and varied in approach with a range of activities in each lesson that fostered communicative and collaborative skills. The findings imply improved cultural knowledge and awareness of local content did provide learners with ideas to harness which subsequently leads to improved communicative ability.